Fashion show presentation in the Philippines - Loyola, Cornelio V. Jr.; Elumba, Ma. Patricia S. (2002.)
This study is an attempt to study the existing practices; expertise and elements in fashion show presentation in the Philippines. This study is significant to the Clothing Technology program because fashion shows are integral to the practice of fashion design and fashion merchandising which supports the competencies of CT majors. The study uses purposive sampling in learning the specific expertise in producing fashion shows. Moreover, the interviews and questionnaires will be given out to the staff and fashion show producers and coordinators of the events production offices to have the information about the existing practices, expertise and elements in fashion show presentation in the Philippines. Robby Carmona, Ariel Lozada, Jackie Aquino, Joey Espino and their corresponding staff were the respondents for this study. The respondents are limited to such number due to the reason that they are the top fashion show directors/producers in the country. The fashion show coordinator performs a great deal of coordinating people and theatrical elements to come up with a successful fashion show. Thus, a clothing technologist who wishes to enter this kind of career might not be qualified due to the reason that his field of expertise is about garments and, also, he has no background in dealing with coordination of the staff and theatrical elements. However, if the clothing technologist would still want to involve himself in fashion show, he can still excel as a fashion stylist.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Fashion shows -- Philippines